A structural equation model of mental health literacy, psychological factors and mental health help-seeking intention among undergraduate students in Health Campus, Universiti Sains Malaysia - Shuan, Deborah Quah Ju (2020)
The rate of mental health help-seeking from formal sources such as doctors, social workers, counselors, psychologists or psychiatrists is low in undergraduate students, despite reports of worsening mental health in recent years. Using intention to as gauge for behavior, this study looks into the effects of mental health literacy and psychological factors (attitude, perceived public stigma, self-stigma and psychological distress) on mental health help-seeking intention. The main aim of this study is to determine the structural relationship between mental health literacy, attitude, perceived public stigma, self-stigma, and psychological distress with mental health help-seeking intention among undergraduate students in Health Campus, Universiti Sains Malaysia (USM). A cross sectional study using self-administered questionnaire was conducted among undergraduate students in Health Campus, USM. Study participants were selected by means of convenience sampling. Confirmatory factor analysis was performed to ensure the questionnaires used were valid and reliable to measure the study variables, and structure equation modelling was performed to determine the path relationships between the variables. A total of 755 undergraduate students participated in this study. For the measurement model of mental health literacy, the final model which consisted of 21 items fit the data well based on the fit indices (Comparative Fit Index (CFI) = 0.949, Tucker-Lewis Index (TLI) = 0.942, Weighted Root-Mean-Square Residual (WRMR) = 1.091, Root Mean Square Error of Approximation (RMSEA) (90% CI) = 0.027 (0.021, 0.033), RMSEA p-value = > 0.950). As for the Attitude Towards Seeking Professional Psychological Help-Short Form (ATSPPH-SF), the second-order two factor scale showed relatively good model fitness (CFI = 0.936, TLI = 0.913, Standardized Root-Mean Square Residual (SRMR) = 0.039, RMSEA (90% CI) = 0.045 (0.033, 0.057), RMSEA p-value = 0.752). The Perceived Devaluation-Discrimination (PDD) scale showed good model fitness (CFI = 0.968, TLI = 0.948, SRMR = 0.024, RMSEA (90% CI) = 0.056 (0.038, 0.074), RMSEA p-value =0.200), after removing three items from the original scale and adding correlations between items. The 8-item Self-Stigma of Seeking Help (SSOSH) scale with correlated items had excellent model fitness (CFI = 0.969, TLI = 0.950, SRMR = 0.029, RMSEA (90% CI) = 0.042 (0.025, 0.059), RMSEA p-value = 0.770). The Kessler Psychological Distress Scale (K10) showed acceptable model fitness (CFI = 0.955, TLI = 0.935, SRMR = 0.034, RMSEA (90% CI) = 0.080 (0.68, 0.091), RMSEA p-value < 0.001). The final structural model had an excellent fit based on the fit indices (CFI = 0.946, TLI = 0.939, SRMR = 0.063, RMSEA (90% CI) = 0.038 (0.034, 0.042), RMSEA p-value > 0.950). The final structural model supported eight hypotheses showing direct and indirect relationship between the study variables. The variables attitude, perceived public stigma and self-stigma have interrelationship between each other to predict help-seeking intention. Meanwhile, mental health literacy has direct effect on help-seeking intention, and indirectly through attitude and self-stigma. Conclusion: Findings of this study suggest that help-seeking intention may be enhanced (directly and indirectly) by improving mental health literacy. Therefore, it is vital that accurate and complete information about mental disorders and treatment resources, and reinforcement of positive attitude or beliefs are provided to the undergraduate students.